Advances in Production Management Systems. The Path to Intelligent, Collaborative and Sustainable Manufacturing : IFIP WG 5.7 International Conference, APMS 2017, Hamburg, Germany, September 3-7, 2017, Proceedings, Part II /: IFIP WG 5.7 International Conference, APMS 2017, Hamburg, Germany, September 3-7, 2017, Proceedings, Part II. (2017) - Unknown
No abstract available